Observations of plasmons in warm dense matter. - Glenzer, S; Landen, O; Neumayer, P; Lee, R; Widmann, K; Pollaine, S; Wallace, R; Gregori, G; Höll, A; Bornath, T; Thiele, R; Schwarz, V; et al. (2007)
We present the first collective x-ray scattering measurements of plasmons in solid-density plasmas. The forward scattering spectra of a laser-produced narrow-band x-ray line from isochorically heated beryllium show that the plasmon frequency is a sensitive measure of the electron density. Dynamic structure calculations that include collisions and detailed balance match the measured plasmon spectrum indicating that this technique will enable new applications to determine the equation of state and compressibility of dense matter.